Advances in Transportation Geotechnics IV Proceedings of the 4th International Conference on Transportation Geotechnics Volume 1 - Tutumluer, Erol.; Nazarian, Soheil; Al-Qadi, Imad.; Qamhia, Issam I.A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This volume presents selected papers presented during the 4th International Conference on Transportation Geotechnics (ICTG). The papers address the geotechnical challenges in design, construction, maintenance, monitoring, and upgrading of roads, railways, airfields, and harbor facilities and other ground transportation infrastructure with the goal of providing safe, economic, environmental, reliable and sustainable infrastructures. This volume will be of interest to postgraduate students, academics, researchers, and consultants working in the field of civil and transport infrastructure. .
Chapter 1: A Conceptual System Dynamics Framework to Evaluate Performance of Pavement Foundations under Moisture Hysteresis -- Chapter 2: Dynamic response of a beam on a layered half-space with a poroelastic interlayer subjected to moving loads -- Chapter 3: Modification of Japanese pavement fatigue life criteria by considering climate effect in cold regions -- Chapter 4: Influence of braking on the pavement shakedown limits -- Chapter 5: Physical modeling of stress propagation in railway pavement with LWD -- Chapter 6: Verification of the structural design parameters for unbound layers of Finnish road structures -- Chapter 7: FreeHyTE: a hybrid-Trefftz finite element platform for poroelastodynamic problems -- Chapter 8: A Mechanistic-Based Analysis Procedure for Designing Geosynthetic Reinforcement in Pavement Systems -- Chapter 9: Geotechnical characterization of a low volume traffic road -- Chapter 10: Development of Prediction Models for Mechanistic Parameters of Granular Roads Using Combined Non-Destructive Tests -- Chapter 11: Influence of Foundation Layer Properties in a Roller-Compacted Concrete Pavement System Subjected to Heavy Vehicle Loads -- Chapter 12: R-Value and Resilient Modulus Prediction Models Based on Soil Index Properties for Colorado Soils -- Chapter 13:Performance Evaluation of Flexible Pavements with Asphalt-treated Base Courses.
Keywords: Engineering geology; Geotechnical engineering; Transportation engineering; Traffic engineering; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Transportation Technology and Traffic Engineering; Engineering geology -- Congresses; Transportation engineering -- Congresses